2015
DOI: 10.1155/2015/632647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Friction Model and Tire Maneuvering on Tire-Pavement Contact Stress

Abstract: This paper aims to simulate the effects of different friction models on tire braking. A truck radial tire (295/80R22.5) was modeled and the model was validated with tire deflection. An exponential decay friction model that considers the effect of sliding velocity on friction coefficients was adopted for analyzing braking performance. The result shows that the exponential decay friction model used for evaluating braking ability meets design requirements of antilock braking system (ABS). The tire-pavement contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 11 publications
1
23
0
2
Order By: Relevance
“…When a tire is subjected to static loads, its convex tread arc and large sidewall deformation lead to maximum stress distribution on the central rib [21][22][23][24]. Since the tread is a rubber extrusion, longitudinal and transverse stresses in the tire are generated in the contact area.…”
Section: Simulation and Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When a tire is subjected to static loads, its convex tread arc and large sidewall deformation lead to maximum stress distribution on the central rib [21][22][23][24]. Since the tread is a rubber extrusion, longitudinal and transverse stresses in the tire are generated in the contact area.…”
Section: Simulation and Test Resultsmentioning
confidence: 99%
“…The areas can be approximated as a trapezoid. The larger load may be approximated as a saddle shape [15,21]. The distribution curves of the tangential force are shown in Fig.…”
Section: Simulation and Test Resultsmentioning
confidence: 99%
“…It's uniquely determined by the friction area size, normal loads and friction coefficient. The above coefficient, which is the frictional rest estimation rate, is usually more than motion friction coefficient for the same surface [9].…”
Section: Methodsmentioning
confidence: 99%
“…The analysis revealed that one way to pit trucks efficiency upgrading in open pits tight working space is the trucks maneuvering abilities improvement [9]. At AC electric traction drive the automatic control system allows to control the motor's rotation forcibly and individually for the rear wheel of starboard and port side if it's necessary to rim pulls difference increasing, which provides additional yaw moment also creating the so-called phenomenon of "additional forced turn" as the vehicle maneuver benefit.…”
Section: Introductionmentioning
confidence: 99%
“…is study was meaningful in terms of research aspect. e three-dimensional stress distribution of heavy-duty truck tires under various rolling conditions was obtained, and it pointed out that the critical slip ratio was around 18%, the braking force reached its maximum [10], whereas the critical slip rates for acceleration and braking state were not compared. A widebase tire was modeled by Hernandez and Al-Qadi [11] to predict contact stress.…”
Section: Introductionmentioning
confidence: 99%